Finance for integrated landscape management. De-risking smallholder farmer investments in integrated landscape management - Byakagaba P.; Nantongo, P.K.; Kalibwani, F. (Tropenbos International, 2021)
The report is part of a series of case studies that provide insights into various mechanisms used to increase access to finance for smallholder farmers, SMEs and communities in their efforts to contribute to sustainable landscapes. The case studies focus on the strategies used by various stakeholders to reduce the risks of selected financial flows for investors, intermediaries and recipients. These case studies follow up on recommendations made by participants in the consultative process on innovative finance for sustainable landscapes. The goal is to provide more evidence of successful strategies in order to increase access to finance for smallholder farmers, SMEs and communities. This case study describes a conservation finance mechanism implemented by the Environmental Conservation Trust of Uganda (ECOTRUST). The mechanism delivers US$6 of every US$10 to smallholder conservation farmers through a blended model that combines public (donor) finance, private-sector foreign direct investment (FDI), and community contributions, to support long-term biodiversity and climate change outcomes at the local level. ECOTRUST has developed this model over 17 years of implementing its Trees for Global Benefit (TGB) program.